EXPLORING CAUSES AND ALLEVIATING STRATEGIES OF ENGLISH STUDENT-TEACHERS’ WRITING ANXIETY AT PATTIMURA UNIVERSITY - Hellien J Loppies (JURNAL TAHURI, 2020)
There have been couples of studies reporting on English students-teachers’ writing anxiety. However, there has been little information on what factors contribute to Indonesian EFL Pre-service teachers’ writing anxiety and how they overcome it. This study aimed at figuring out the facts of related causes of anxiety and alleviating strategies that English student-teachers in English teachers at Pattimura University Ambon employ when they write in English language. The research design is both quantitative and qualitative methods. The data were collected from questionnaires and in-depth interview. The results reveal some contributing factors to participants’ writing anxiety including linguistic difficulties, time pressure, lack of writing practices, instructors’ evaluation and pressure for a perfect work. Furthermore, to overcome their problems, the participants utilize the rethorical, cognitive and socio-affective strategies. The study, then, concludes that by recognizing the causes of writing anxiety, the participants may work better on applying strategies that can reduce their level of writing anxiety